2006
DOI: 10.1590/s0101-81752006000400031
|View full text |Cite
|
Sign up to set email alerts
|

Biologia populacional das espécies de Ampithoidae (Crustacea, Amphipoda) associadas a Sargassum filipendula (Phaeophyta, Fucales) na Praia da Fortaleza, Ubatuba, São Paulo, Brasil

Abstract: A biologia populacional de três espécies de anfípodes da família Ampithoidae (Ampithoe ramondi, Cymadusa filosa e Sunampithoe pelagica) associadas a Sargassum filipendula da Praia da Fortaleza, litoral norte do Estado de São Paulo foi estudada entre junho de 2000 e maio de 2001. Os anfípodes foram identificados, contados e separados em classes de tamanho através de um conjunto de peneiras agrupadas. Foram obtidos histogramas mensais de jovens, machos e fêmeas. A razão sexual dos ampitoídeos foi avaliada mensal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
19

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 46 publications
1
14
0
19
Order By: Relevance
“…This is the case with gammarid amphipods of the families Ampithoidae and Hyalidae, for which there are reports of the utilization of epiphytes and Sargassum (Zimmerman et al, 1979;Duffy, 1990;Duffy & Hay, 1994). For the Sargassum beds on São Paulo coast, there are five hyalid and three ampithoid species of amphipods reported (Tararam & Wakabara, 1981;Wakabara et al, 1983;Leite et al 2000;Jacobucci & Leite, 2006). Some of these species had its feeding habits evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case with gammarid amphipods of the families Ampithoidae and Hyalidae, for which there are reports of the utilization of epiphytes and Sargassum (Zimmerman et al, 1979;Duffy, 1990;Duffy & Hay, 1994). For the Sargassum beds on São Paulo coast, there are five hyalid and three ampithoid species of amphipods reported (Tararam & Wakabara, 1981;Wakabara et al, 1983;Leite et al 2000;Jacobucci & Leite, 2006). Some of these species had its feeding habits evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…A composição da fauna de decápodes associada à Sargassum foi semelhante às de áreas continentais do Estado de São Paulo (Jacobucci et al 2006) . A praia de Santa Rita é menos diversa (H') do que a praia do Flamengo (Anova, F=7,856 p=0,00613).…”
Section: Resultsunclassified
“…Yet some environmental and biotic factors, could also have contributed for that, for example, a greater susceptibility of one of the genders to predation, which is directly related to the difference in sizes and behaviour. Although females of Crangonyx pseudogracilis are larger than males, males must find females to mate, thus being more exposed to predators (Jacobucci and Leite, 2006;Castiglioni et al, 2016). Additionally, a study by Watts et al (2002) revealed that the exposure of amphipods to certain chemicals present in the residual water, such as 17a À ethinylestradiol or also known as environmental estrogen (EE), can favour females more than males, resulting in a marked difference in proportions between the genders.…”
Section: Discussionmentioning
confidence: 99%